Trade Supervision Through the Government Electronic System Based on Law No. 7 Of 2014 Concerning Trade And Government Regulation No. 80 of 2019 Concerning Trade Through Electronic Systems - Ailsa Salma Indrasari (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
The rapid development of technology changes people's lifestyles, including trade transactions. This research discusses the regulation of trade through electronic systems based on Law No. 7 of 2014 on Trade and Government Regulation No. 80 of 2019 on Trading Through Electronic Systems as well as preventive and repressive efforts by the government in order to supervise the implementation of trade transactions through electronic systems or e-commerce based on PP No. 80 of 2019 on Trading Through Electronic Systems. The methods used are arranged systematically, logically, and rationally. In the sense that the entire data obtained will be connected adjusted to the subject matter examined. Regulation on trading through electronic systems or e-commerce under the mandate of Article 66 of Law No. 7 of 2014 on trade is contained in Government Regulation No. 80 of 2019 on Trading Through Electronic Systems. In Government Regulation No. 80 of 2019 concerning Trade Through Electronic Systems, the government seeks guidance as a preventive effort and implements administrative sanctions as a repressive effort on perpetrators of violations of applicable rules and regulations. The government should make trade arrangements through electronic systems to not overlap with other rules and conduct further guidance on trading businesses through electronic systems. Keywords: Regulations, Supervise, E-commerce